A Retrospective Interventional Cohort Study to Assess the Safety and Efficacy of Sandostatin LAR for Treatment of Recurrent and/or Refractory Meningiomas - Hrachova, Maya; Nguyen, Emely Nhi T.; Fu, Beverly D.; Dandekar, Manisha J.; Kong, Xiao-Tang; Cadena, Gilbert; Hsu, Frank P. K.; Billimek, John; Taylor, Thomas H.; Bota, Daniela A. (Frontiers in Neurology, 2020)
Background: Meningiomas are the most common adult primary intracranial tumors in the United States. Despite high recurrence rate of atypical and malignant subtypes, there is no approved drug indicated specifically for meningioma. Since the majority of meningiomas exhibit high density of somatostatin receptors subtypes, somatostatin analogs have been under close investigation. The aim of this study was to evaluate efficacy and safety of Sandostatin LAR (octreotide) in patients with progressive, and/or recurrent meningioma, and identify subset of patients who were more likely to benefit from this treatment. Methods: A total of 43 patients ≥ 18 years old were included in the retrospective chart review. The patients underwent treatment with Sandostatin LAR (octreotide) from 01.01.2010 to 06.01.2017 at the University of California, Irvine after confirmation of the diagnosis. Six months progression free survival (PFS6) was defined as a primary endpoint, and the overall survival (OS), safety, and toxicity were identified as secondary endpoints. Results: The OS for 6 months, 1, and 3 years for all WHO grades was 94.8, 88.1, and 67.0%, respectively. The PFS6 for WHO I, II, III, and all was 89.4, 89, 33.3, and 80% respectively. For patients with no prior surgeries, chemotherapy or radiation, the PFS6 was 88.9, 84.8, and 94.8%, respectively. Interestingly, the PFS6 was 90.5% for skull-based and 80% for 3–6 cm tumors. Patients with tumors in parasagittal location had PFS6 of 83.3% compared to PFS6 of 50.0% for patients with convexity tumors. Evaluation of PFS6 based on the effect of estrogen and progesterone on meningioma identified that ER-PR+ tumors had PFS6 of 87.8% while patients with ER-PR- meningiomas had PFS6 of 62.5%. Median TTP for WHO grade I, II, and III was 3.1, 2.40, and 0.26 years, respectively. Subgroup analysis showed that median TTP was 3.1 years for <3 cm tumors, 3.22 years for skull-based tumors, 2.37 years for patients with prior surgeries and 3.10 years for patients with no history of chemotherapy. History of radiation had no effect on median TTP. Sandostatin LAR (octreotide) was well-tolerated. Conclusions:This is one of the largest retrospective analysis of meningioma patients treated with Sandostatin LAR (octreotide) suggesting that this treatment has minimal to no adverse events and could prolong overall survival, and progression free survival especially for patients with ER-PR+ tumors who underwent surgeries for small skull-based tumors.